Fenomena Hari Tanpa Bayangan Sebagai Penanda Awal Waktu Salat Dzuhur di Kabupaten Enrekang - Amelia, Andi Mulia; irfan; Permana, Imam (HISABUNA: Jurnal Ilmu Falak, 2023)
This study aims at 1) to find out the stages of the process do not appear to be solar shadows in a shadowless phenomenon of days, 2) to learn of a shadowless phenomenon in verifying the beginning of the time when the Dzuhur sciene perspective. this type of research is "field research" with the shar’i and astronomy. the study was at 12.11 to 12.13 that the sun’s reflection on perpensive objets was still vicible, and at 12.15 the sun’s reflection was virtually absent from perpension, indicating that the shadowless phenomenon of the day was taking place. so that the shadowless day phenomenon occurred in the district of Enrekang at 12/15 and if the beginning of the time is wrong before or while this phenomenon is taking place it is a false time, for the beginning of the true Dzuhur salat time was sometime after this shadowless day phenomenon occurade. research focused on the shadowless and early days of the Dzuhur’s greetings. this research is ina field that can affect several complex factors, which is why expexted that skilled falak academics and institution could do conforg research in harmony with modern science entirely at a possible point where there is a discrepancy in the appearance of shadowless day phenomena. keywords : A day without shadow, A timer, Dzuhur.